EXPLORING A PEER SUPPORTER’S EMOTIONAL GEOGRAPHIES IN SUPPORTING STUDENTS WITH DISABILITIES (SWD) - Dafifah, Alfiyya; Sudarwati, Emy (Universitas Islam Sumatera Utara (UISU), 2025)
This study explores the emotional geography of a peer supporter who assists students with disabilities at Brawijaya University. Data were obtained from a participant at the Disability Service Center (PSLD) with the informed consent of the individual involved. The data were collected over three months through in-depth interviews. The analysis draws upon Hargreaves’ (2001) framework of five emotional geographies—moral, sociocultural, physical, professional, and political. The study aims to analyze the emotional relationships that emerge during the peer support program organized by PSLD UB in assisting students with disabilities (SWD) as they navigate university life. The findings reveal how a peer supporter contributes to the academic and moral well-being of SWD, not only by providing physical support but also through emotional engagement. Furthermore, the study uncovers how the peer supporter responds to various situations with empathy, resilience, initiative, and responsiveness. These findings highlight the importance of fostering both personal and professional growth among peer supporters to strengthen inclusive practices within higher education environments.